2020
DOI: 10.1080/15384101.2020.1784599
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates inflammation and cell apoptosis through regulating NF-κB and JAK2/STAT3 signaling pathway against acute kidney injury

Abstract: Curcumin alleviates septic acute kidney injury (SAKI); however, the underlying mechanism remained unclear. To explore this, SAKI cell model and mice model were conducted by using LPS and cecal ligation and puncture (CLP), respectively. Cell counting kit-8 (CCK-8) and enzyme-linked immunosorbent assay (ELISA) assays indicated that LPS reduced the viability, but upregulated the levels of tumor necrosis factor (TNF)-α and interleukin (IL)-6, whereas Curcumin pretreatment had no effect on viability, but reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…As expected, our results elucidated that IQC normalized cisplatin-induced increase of inflammatory markers. A previous investigation demonstrated that p65 is involved in cisplatin mediated renal toxicity (Zhu et al, 2020). Here, we also observed that IQC decreased the upregulation of both p65 and P-p65.…”
Section: Discussionsupporting
confidence: 84%
“…As expected, our results elucidated that IQC normalized cisplatin-induced increase of inflammatory markers. A previous investigation demonstrated that p65 is involved in cisplatin mediated renal toxicity (Zhu et al, 2020). Here, we also observed that IQC decreased the upregulation of both p65 and P-p65.…”
Section: Discussionsupporting
confidence: 84%
“…The change in TLR9 expression is usually considered to be a sign of the development of various inflammation-related diseases, while Cur can reduce TLR9 expression in the rat liver and act as an antiinflammatory and immunomodulatory agent to treat liver inflammation (28). The most recent study has revealed that Cur could ameliorate the SAKI induced by CLP, but they only detected the kidney protective effect of the Cur (29). While in this paper, we have found that the Cur could significantly decrease the mortality caused by AKI, and we also determined that Cur could prevent multiple organs from dysfunction caused by AKI, meanwhile, our results were almost based on the in vivo data, which may be more coincidence with the pathogenesis of AKI in human.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the phosphorylated activation of JAK2/STAT3 played a part in the induction of apoptosis, autophagy, inflammation, and oxidative stress and that the activation of the JAK2-STAT3 signaling pathway protected tissue against acute injury in some studies (35)(36)(37). In contrast, the renoprotective effect of curcumin in AKI caused by lipopolysaccharide (LPS) or severe acute pancreatitis may be associated with inflammation reduction mediated by suppression of JAK2/STAT3 signaling pathway (38,39). In our study, increased phosphorylation of JAK2/STAT3 after EPO treatment alleviated CIN by ameliorating cell apoptosis and pyroptosis in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%